Single-Lumen Endotracheal Tube and Bronchial Blocker for Airway Management During Tracheobronchoplasty for Tracheobronchomalacia: A Case Report. Issue 6 (15th September 2019) - Lui, Natalie S.; Guo, Haiwei Henry; Sung, Arthur W.; Peterson, Ashley; Kulkarni, Vivekanand N.
Abstract : We present a case of a 69-year-old man who underwent tracheobronchoplasty for tracheobronchomalacia using a single-lumen endotracheal tube and a Y-shaped bronchial blocker for airway management. Tracheobronchoplasty is performed by sewing mesh to plicate the posterior, membranous wall of the distal trachea and main bronchi through a right posterolateral thoracotomy. The goals of airway management include continuous left-lung ventilation and lung protection from aspiration. Ideally, only conventional airway management tools are used. This case demonstrates that a single-lumen endotracheal tube with a bronchial blocker can be a straightforward strategy for airway management during tracheobronchoplasty.